Peran media dalam meningkatkan efektivitas belajar - Anwar Ramli; Rahmatullah Rahmatullah; Inanna Inanna; Taslim Dangnga (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This paper aims to provide understanding to students of the Teacher Certification Program (PPG) on the importance of developing learning media as an effort to improve the process and quality of learning in schools. This training was carried out in the form of instructional media training that lasted for two days starting on August 4-5 2018. The material presented in this training consisted of two main themes, the basic concepts of learning media and the practical exercises in developing a learning media. This training involved 14 students of Teacher Certification Program in the Economic Education Study Program at Universitas Negeri Makassar. The material delivery method of the training consists of the lecturing, question and answer session, discussion and drill.